GAMBARAN KECEMASAN IBU HAMIL TERHADAP PAPARAN ASAP ROKOK DI DESA KARYAMUKTI KECAMATAN RIMBA MELINTANG KABUPATEN ROKAN HILIR - Titik Pratiwi; Yulia Irvani Dewi; Sri Wahyuni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Smoking during pregnancy can be harmful to the development of the fetus in the womb. Pregnant women who smoke or are exposed to secondhand smoke will cause various complications such as birth (premature), low birth weight, perinatal mortality and impaired fetal development. The research design used is descriptive quantitative. The research sample was 100 respondents using Accidental Sampling sampling technique.The results showed that the majority of research subjects were in the age range of late adolescence (17-25 years) as many as 48 respondents (48%), most of them were in the second trimester with 23 respondents (23%) and most of them were multiparous, namely 44 respondents ( 44%).The results showed that the majority of respondents experienced mild anxiety.Keywords: Anxiety, Pregnancy, Smoking.